Magnetic Properties of xCeO2·(50-x) PbO·50B2O3 Glasses and Glass Ceramics - Damrawi, G.El; Gharghar, F. (JOURNAL OF ADVANCES IN PHYSICS, 2017)
Cerium oxide in borate glasses of composition xCeO2·(50 − x)PbO·50B2O3 plays an important role in changing both microstructure and magnetic behaviors of the system. The structural role of CeO2 as an effective agent for cluster and crystal formation in borate network is clearly evidenced by XRD technique. Both structure and size of well-formed cerium separated clusters have an effective influence on the structural properties. The cluster aggregations are documented to be found in different range ordered structures, intermediate and long range orders are the most structures in which cerium phases are involved. The nano-sized crystallized cerium species in lead borate phase are evidenced to have magnetic behavior. The criteria of building new specific borate phase enriched with cerium as ferrimagnetism has been found to keep the magnetization in large scale even at extremely high temperature. Treating the glass thermally or exposing it to an effective dose of ionized radiation is evidenced to have an essential change in magnetic properties. Thermal heat treatment for some of investigated materials is observed to play dual roles in the glass matrix. It can not only enhance alignment processes of the magnetic moment but also increases the capacity of the crystallite species in the magnetic phases. On the other hand, reverse processes are remarked under the effect of irradiation. The magnetization was found to be lowered, since several types of the trap centers which are regarded as defective states can be produced by effect of ionized radiation.